HYDROCARBON EMISSIONS DISCLOSURE: A STRATEGIC PREDICTOR OF RETURN ON INVESTMENT IN THE NIGERIAN ENERGY INDUSTRY (Journal of Global Accounting, 2025)
The study examined the effect of hydrocarbon disclosure on the return on investment of listed energy firms in Nigeria. Ex-post facto research design was deployed. The population comprised eight (8) listed oil and gas firms in Nigeria. A sample size of seven (7) firms were selected using purposive sampling technique. Secondary data were collected from firms’ annual reports over a ten year period (2015-2024). The data were analysed using descriptive test while hypotheses were tested using panel estimated generalised least square regression. The findings revealed that hydrocarbon emission disclosure has a positive and significant effect on return on investment of listed energy firms in Nigeria (β = 0.073859, p = 0.0056). This indicates that environmental accountability is gaining economic weight in the investment calculus, suggesting a broader market recognition that sustainability and profitability are not mutually exclusive but potentially reinforcing dimensions of firm performance in resource-dependent economies. It is therefore recommended that the management boards of listed energy firms in Nigeria institutionalize standardized hydrocarbon emission disclosure frameworks within their annual reporting processes to strengthen market confidence, enhance investor trust, and leverage transparency as a driver of sustained financial returns.
Keywords: Energy Firms; Hydrocarbon Emission Disclosure; Return on Investment